Collective Perceptions of Aging and Older Persons Held by Students From Eight Healthcare Professions. (March 2022) - Fisher, Kelly; Watson, Jennifer; Willis, Jada L.; Hawley, Diane; Severance, Jennifer; Butler Carroll, Traci; Jackson, Lynn
In order to increase the number of students entering the geriatric workforce, an understanding of factors influencing career preference and what may prevent students from pursuing geriatric careers is necessary. Using a convergent parallel mixed methods approach, the aim of this study was to provide insight for geriatric educators regarding the collective perceptions of aging and older persons held by 864 students from eight healthcare professions. Quantitative questions assessed students' attitudes (Geriatric Attitudes Scale). Student responses to four open-ended questions were assessed using conventional content analysis. Results included rich narrative examples of healthcare professions students' perceptions and understanding of the aging process, as well as myths and misconceptions of aging and older persons that can be used to inform geriatric curricula across multiple health professions training and education programs. Geriatric education is a critical avenue to correct misperceptions, quell ageism and address the current shortage in the geriatrician workforce.